Nellautaijub Jesaiasib aglangit [electronic resource]. - Martin, A. (Herrnhut [Germany] : G. Winterib nênilauktangit, 1903)
"Printed for the British and Foreign Bible Society in London for the use of the Moravian mission in Labrador." "A new edition of Isaiah, revised by A. Martin, superintendent of the Labrador mission, with the help of the Hebrew, the revised English and German versions, and Kleinschmidt's translation in Greenland Eskimo"--Darlow & Moule. National Union Catalog pre-1956 imprints, Evans, K. Masinahikan (Toronto, 1985), Darlow & Moule Electronic reproduction. Mode of access: Internet. 44